Myricetin prevents dopaminergic neurons from undergoing neuroinflammation-mediated degeneration in a lipopolysaccharide-induced Parkinson's disease model. (June 2018) - Huang, Bingxu; Liu, Juxiong; Ma, Dongxu; Chen, Guangxin; Wang, Wei; Fu, Shoupeng
Graphical abstract: Highlights: Myricetin treatment inhibits the activation of microglia and protects the dopaminergic neuron in PD rats. Myricetin suppresses microglia-mediated neurotoxicity. The neuroprotective mechanism of myricetin is explained. Abstract: Myricetin, one of the lipophenolic compounds present in red wine, has been reported to pass through blood–brain barriers and reduce dopaminergic neuron degeneration, but the mechanism remains unclear. We thoroughly investigated the underlying mechanisms in Parkinson's disease models both in vivo and in vitro . The neuroprotective effects of myricetin were assessed by performing behavioural test, immunohistochemistry and western blotting in vivo . The expression of pro-inflammatory mediators in the rat' substantia nigra was examined using qPCR and ELISA. The toxicity of conditioned medium from BV-2 cells towards SH-SY5Y dopaminergic neuronal cells was measured by MTT assay in vitro . The myricetin treatment suppressed the activation of microglia, the expression of pro-inflammatory mediators and the reduction in the number of dopaminergic neurons and ameliorated the rats' motor dysfunction. Mechanistically, myricetin inhibited the production of pro-inflammatory mediators and the activation of the MAPK and NF-κB pathways in activated microglia. Based on these results, myricetin prevents dopaminergic neuron degeneration by inhibiting microglial neuroinflammation.